Strength and Aerobic Physical Exercises Are Able to Increase Survival of Toxoplasma gondii-Infected C57BL/6 Mice by Interfering in the IFN-γ Expression - Bortolini, Miguel J. S.; Silva, Murilo V.; Alonso, Fábio M.; Medeiros, Luciana A.; Carvalho, Fernando R.; Costa, Lourenço F.; Silva, Neide M.; Penha-Silva, Nilson; Mineo, Tiago W. P.; Mineo, José R. (Frontiers in Physiology, 2016)
Physical exercise has been implicated in several immunophysiological improvements, particularly during the aging process, when an immunocompromised status could be established. Toxoplasma gondii is a protozoan parasite that causes a widespread opportunistic infection, which may present severe consequences, mainly to the fetus and immunocompromised patients. It is estimated that one-third of the human population worldwide has been infected by this parasite, being the reactivation during immunesenescence an unexplored public health issue. The major purpose of the present study was to observe the immunophysiological differences between exercised versus sedentary C57BL/6 male mice that have been experimentally infected by T. gondii. In the first set of experiments, the animals were infected after exercising and three groups were set up: experimental groups - infected sedentary (IS, n=6); infected exercised (IEx, n=6) and control group - non-infected sedentary (NIS, n=6). When stimulated in vitro by T. gondii-soluble tachyzoite antigen, it was found that splenocytes from exercised group produced higher levels of IFN-, as well as of IFN-/IL-10 ratios in comparison with splenocytes from sedentary animals (P<0.001). However, it was not found significant differences concerning quantification of T. gondii genomic DNA by qRT-PCR and immunohistochemistry analysis in brain cysts from both group of animals (P>0.05). In order to further investigate the consequences of these data for the host, a second set of experiments was performed, when the animals were infected before exercising and four groups of animals were established for comparison purpose, as follows: experimental groups - infected sedentary (IS, n=7); infected exercised (IEx, n=6) and control groups - non-infected sedentary (NIS, n=6) and non-infected exercised (NIEx, n=6). It was found significant differences in the survival rates of the exercised group the animals, as they survived longer than sedentary groups (P=0.0005). In both sets of experiments, mice have been submitted to moderate exercises: aerobic (14m/min; 3x/week) and strength (60-80% of one maximum repetition; 2x/week). Overall, our findings are showing that the aerobic and strength exercises are able to modulate immune response against T. gondii infection, being these immunological features beneficial to the host.